Budidaya Hidroponik Pakcoy Berbasis Barang Bekas: Solusi Urban Farming Inovatif dalam Mendukung Ketahanan Pangan Keluarga - Siti Nuurlaily Rukmana; Intan Nur Fitriana; Panji Dwi Kusuma; Nanda Jovita; Muhammad Muchlis; Shakila Aulia Putri; Dinda Kusuma Putri; Nadila Resti Octaviani; Cintaka Ardelia Cahyani; Ida Ilham Ramadhan; Intan Riya Febriyanti; Minanto Eko Utomo; Moch Zackiyul Fahmi (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Food security has become a primary concern in Indonesia, as the growing demand for food increasingly collides with the limited availability of agricultural land and the challenges of conventional farming. One innovative solution being developed is hydroponic cultivation, a soil-less farming technique that utilizes alternative media and nutrient-enriched water. This study aims to revitalize the hydroponic system in Kepatihan Village, Sidoarjo, through a community training program on pakcoy cultivation using recycled materials, particularly plastic bottles and PVC pipes. The program was implemented using a management approach consisting of planning, implementation, monitoring, and evaluation stages. The results indicate a significant improvement in participants’ knowledge and understanding of hydroponic farming after the training sessions. Community members were not only able to assemble simple systems made from recycled materials but also successfully cultivated pakcoy sustainably using PVC pipes and repurposed plastic bottles as growing media. Participants demonstrated creativity and innovation by modifying the design of the recycled bottles, reflecting a deeper comprehension of hydroponic principles while promoting recycling practices and reducing plastic waste. Despite the promising outcomes, several challenges were identified, such as pest attacks, nutrient solution contamination, and the need for regular maintenance to achieve optimal yields. Overall, this study demonstrates that hydroponic farming based on recycled materials is not only environmentally friendly and cost-efficient but also represents an inclusive, innovative, and sustainable urban farming practice. Therefore, it can serve as a practical solution to strengthen household food security while fostering community participation in developing modern agricultural systems in urban areas.